THE PROCEDURAL CRIMINAL PROTECTION OF THE JUVENILE DELINQUENT - Al-Abidi, Nihad Ali Malik; Hay, Rami Abdel (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2025)
Objective: Juvenile delinquency presents a significant challenge to legal systems, with varying approaches across countries like Iraq and Lebanon, and this study aims to critically examine the effectiveness of the procedural protections provided to juvenile delinquents in Iraq and Lebanon. Method: Both nations have enacted laws offering procedural protections for delinquent juveniles, but gaps remain in their application, and the research identifies gaps in the law and proposes legislative amendments to enhance juvenile protection through a comparative analysis. Result: Iraq and Lebanon’s legislations have introduced important reforms, including the right to legal representation and confidentiality during trials, as well as the establishment of rehabilitation-focused detention facilities; however, the research reveals that these measures have not fully achieved the goal of distinct juvenile treatment compared to adults, and both countries have insufficient measures for post-release care and extended detention periods for juveniles. Despite existing protections, legislative frameworks in both countries have not sufficiently distinguished juvenile offenders from adults in a way that addresses their unique needs, and the study suggests that while both systems have some rehabilitative provisions, they need to integrate preventive measures and clearer legal guidelines. Novelty: The novelty lies in the comparative analysis of Iraq and Lebanon’s juvenile protection systems, identifying significant areas for reform, including the need for specialized juvenile defense attorneys and improvements in post-conviction care, underscoring the necessity for legal reforms that provide better protection and rehabilitation for juvenile delinquents, emphasizing the importance of legislative clarity and the integration of preventive measures to reduce recidivism.